The benefits of a peer‐assisted mock PACES. (14th June 2017) - Siddiqui, Sarim; Siddiqui, Samee; Mustafa, Qamar; Rizvi, Abeer F; Hossain, Ibtesham T
Summary: Background: Peer‐assisted learning (PAL) and mock examinations have been credited as effective teaching tools; however, there is a lack of research into their effectiveness in PACES (practical assessment of clinical examination skills). This study demonstrates an effective model and the benefits of PAL after its implementation in a mock PACES at Imperial College London. There is a lack of research into the effectiveness of PAL and mock examinations in PACES Methods: A mock PACES was designed for fifth‐year medical students. Examiners were recruited from the final year and from the foundation year doctor (intern) cohort. A Likert scale (1, strongly disagree; 5, strongly agree) questionnaire given before and after the exam was used to investigate its effectiveness. Results: A total of 41 pre‐mock exam surveys (57% completion rate) and 57 post‐mock exam surveys (79% completion rate) were completed. Students felt significantly more confident after the mock PACES (mean 3.54 post‐mock exam versus 2.68 pre‐mock exam), with 90.64 per cent of students agreeing that this mock PACES was more useful than a lecture‐based format, bedside teaching and small group teaching in order to prepare for this exam. Twenty‐eight tutor surveys were completed (87.5% completion rate). Tutors agreed that the mock PACES had improved their confidence in their teaching ability (mean 4.07) and enhanced their clinical knowledge (mean 4.18). Discussion: The mock PACES demonstrated benefits to confidence levels and knowledge both for tutees and tutors. The results demonstrate an effective model in examination preparation for PACES. This reinforces the holistic positive attributes gained from the use of PAL and mock examinations, whilst encouraging its use within the undergraduate syllabus.